DETERMINING THE LOCATION OF LAND SUBSIDENCE OBSERVATION POINTS BASED ON LITHOLOGICAL DATA AND LAND COVER CHANGES IN LAMPUNG PROVINCE - Perdana, Redho Surya; Fikri, Muhammad; Alif, Satrio Muhammad; Isnaini, Een Lujainatul; Fauzi, Adam Irwansyah (GeoEco, 2022)
Land subsidence is a phenomenon that always occurs due to natural factors as well as human actions. Land subsidence has an even impact on all fronts. Land subsidence occurs continuously, therefore it is necessary to observe the phenomenon of land subsidence periodically using the GNSS method, which requires a benchmark that serves as a reference point for observation. With the need for a new benchmark devoted to observing land subsidence, it is necessary to do spatial modeling which is useful for finding out the suitability of the location where the subsidence observation point will be made. Spatial modeling was carried out using land cover data and lithology type to then be given weight and score and determined the soil movement vulnerability class into three, namely low class, medium class, and high class. The results of the spatial modeling of subsidence vulnerability show that the area12292.60 square kilometers is low grade, 20230.64 square kilometers represents medium class and 540.32 square kilometers is high class. Based on these results, the planning of the location of new observation points was carried out in areas with moderate to high levels of vulnerability with a total of 87 points scattered throughout the cities in Lampung.